Area variations in the process of care in urban general practice. Issue 6439 (28th July 1984) - Wilkin, D; Metcalfe, D H; Hallam, L; Cooke, M; Hodgkin, P K
Abstract : One hundred and eighty three practitioners collected data on 110 000 consultations. Case mix and pattern of care are compared for doctors practising in different urban areas. Inner city areas are compared with outer areas and the most deprived with the most affluent. Case mix varies slightly between areas, but there are no systematic differences in the pattern of care, which is equally variable in different areas. The stereotype of inner city general practice is not confirmed.